Anemia among children living with HIV/AIDS on HAART in Mekelle Hospital, Tigray regional state of northern ethiopia - a cross-sectional study - Feven Tesfay; Abrha Gebregerges; Haftay Gebrehiwot; Haftu Hailekiros; Letegebriel Girmay; Hadush Bekuretsion; Gebrekidan Gebrezigher; Gebreslassie Gebremariam; Gebreyohannes Teklehaimanot (BMC, 2021)
Abstract Background Anemia is a common complication of HIV/AIDS in children. There is lack of evidence on anemia prevalence among children living with HIV/AIDS on highly active antiretroviral therapy (HAART) in Tigray regional state, which the current study aimed to generate. Methods An institution-based cross-sectional study was conducted on 241 children living with HIV/AIDS on HAART attending the antiretroviral therapy (ART) clinic of Mekelle hospital from November 2018-January 2019. Socio-demographic data were collected using a structured pretested questionnaire. Participants' hemoglobin level was utilized to determine the prevalence of anemia. WHO cut-off values for Hgb were used to categorise the severity of anemia. Microscopic examination was performed for morphological classification of anemia. Results Among the participants, 7 % (n = 16) were anemic in this study. Of these, 56 %, 19 %, and 25 % had mild, moderate, and severe anemia, respectively. Morphologically, normocytic-normochromic anemia was found the most common type of anemia in this study. Conclusions The prevalence of anemia among participants was low in this study. However, a considerable proportion of participants had severe anemia, requiring regular monitoring of anemia status in these patients for better clinical outcomes and quality of life improvements.